KORELASI BIAYA PROMOSI DENGAN VOLUME PENJUALAN PADA PERUSAHAAN JASA BENGKEL BODY REPAIR - Tri Marhaeni; Kusdwiyanto Kusdwiyanto (STIA MALANG, 2023)
Promotion is one of the marketing activities to persuade and influence consumers to be interested in or buy theproducts or services offered by the company, so that it is expected to increase sales volume which in turn is forthe survival of a company. The type of research used is explanatory with a quantitative approach, and the dataanalysis used is bivariate with the help of Product Moment correlation statistics.The results showed that the type of promotion used by the company was WOM, free after-sales service,advertising via radio, newspapers, billboards. The results of the correlation analysis show a positive correlationcoefficient of 1.11 in other words that the relationship between promotion and sales volume is in the perfectand positive category so that the promotion costs incurred by the company have a positive and decisiverelationship, therefore promotional activities should be maintained and in the digitalization era it is better totake advantage of social media